Pemikiran/Pembaharuan Islam KH. Ahmad Dahlan - Azman, Zainal; Helandri, Joni (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This paper will review the thoughts of K.H Ahmad Dahlan, his thoughts were inseparable from the condition of the Indonesian nation at that time, namely being colonized by the Dutch, both in mental and physical form, in the mental form of being duped and in the form of physical peddling, namely forced labor and draining all the nation's resources. From this phenomenon was born the thought of renewal both through the fields of education and da'wah. The research method used is descriptive qualitative research with a library research approach and the results of this study are that the renewal of K.H Ahmad Dahlan through the establishment of the Muhammadiyah organization established educational and da'wah institutions to fight the resistance of the colonial nation for the sake of advancing Islam.